Outside Front Cover: Volume 2 Issue 3. (30th September 2021) - Wang, Xiang; She, Pengfei; Zhang, Qichun
Abstract : Outside front cover image : As numerous scientists seek various strategies to synthesize well‐patterned organic‐ligand‐containing frameworks including metal‐organic frameworks, covalent organic frameworks, and hydrogen‐bonded organic frameworks under a mild condition. Among them, the electrochemically‐induced crystallization and thin film fabrication of organic‐containing frameworks has been demonstrated as one of the most efficient, safe, and facile ways to realize that goal. In this review, mechanisms along with the processing parameters of electrochemically induced crystallization was discussed. The main challenges in this field are expounded as well. Dedicated to Professor Daoben Zhu on the occasion of his 80th Birthday. (DOI: https://doi.org/10.1002/smm2.1057 )